DC/DC Boost Converter Functionality in a Three-Phase IMC (International Journal of Engineering and Computer Science, 2013)
An indirect matrix converter (IMC) connected with two input power sources is proposed: a gasoline generator as themain ac power supply and batteries as the secondary power source. The IMC is small in size because of having a dclink part without an electrolytic capacitor. The dc-link part is utilized by connection with a boost-up chopper with batteries as a secondary input power source. Furthermore, the chopper connects to the neutral point of the motor and utilizes the leakage inductance of the motor as a reactor component. The proposed technique successfully further reduce the size of the converter by removing the boost reactor in the boost converter stage. The proposed converter is simulated and experimentally validated using a 750-W prototype and an induction motor driven with V/f control. The total harmonic distortion of the input and output currents are 4% and 3.7%, respectively,and the efficiency is 96%